The Gambia : Request for a Staff-Monitored Program; Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2019)
This paper discusses The Gambia's request for a Staff-Monitored Program (SMP). The Gambia is enjoying a strong economic recovery, with good prospects of sustained growth over the medium term. In order to consolidate gains and establish a track record for a possible arrangement under the Extended Credit Facility, the authorities are requesting a new SMP covering 2019. The SMP will help build an adequate track record of performance for a potential Fund-supported program. Enhanced domestic revenue mobilization and expenditure control will help create room for much needed public investment and poverty-reducing social spending. The program's strategy includes fiscal policy to focus on domestic revenue mobilization, improved treasury management and spending prioritization. A prudent borrowing strategy and strengthened oversight of state-owned enterprises, with the focus on containing contingent liabilities, is expected to contribute to anchoring debt sustainability. Monetary policy will remain active to curb inflation pressures and banking supervision vigilant to foster financial stability.